The Escherichia coli chromosome moves to the replisome - Gras, Konrad; Fange, David; Elf, Johan (Uppsala University, 2024)
In Escherichia coli, it is debated whether the two replisomes move independently along the two chromosome arms during replication or if they remain spatially confined. Here, we use high-throughput fluorescence microscopy to simultaneously determine the location and short-time-scale (1 s) movement of the replisome and a chromosomal locus in the same cell throughout its cell cycle. The assay is performed for several loci. We find that (i) the two replisomes are confined to a region of ~250 nm and ~120 nm along the cell’s long and short axis, respectively, (ii) the chromosomal loci move to and through this region sequentially based on their distance from the origin of replication, and (iii) when a locus is being replicated, its short time-scale movement slows down. This behavior is the same at different growth rates. In conclusion, our data supports a model with DNA moving towards spatially confined replisomes at replication.

This dataset contains the raw data, analysis and code needed to generate the figures presented in the paper. The raw data consists of microscopy images. The analysis and code consists of analysis code, output from the analysis and its post-processing.

Experimental data, analysis and plot scripts are all organized using unique IDs (UID; seen for example in the filenames of experimental data below). The README.txt file in the Analysis_of_data folder describes which UIDs for data, analysis & figure generation to combine for specific figures/tables.

For the microscopy experiments (has the prefix Microscopy_Data_ in their filenames) there is information on the growth condition, strain genotypes, which positions corresponds to which genotype, and also which figure the data was used in. All experiments were performed at 30 degrees Celsius.

Details on the output from microscopy experiments can be found in the file MicroscopyInformation.txt.
Keywords: Systems biology; Medical and Health Sciences; Medicin och hälsovetenskap; Biological Sciences; Biologi